2003
DOI: 10.1046/j.1432-1033.2003.03462.x
|View full text |Cite
|
Sign up to set email alerts
|

nNOS inhibition, antimicrobial and anticancer activity of the amphibian skin peptide, citropin 1.1 and synthetic modifications

Abstract: A large number of bioactive peptides have been isolated from amphibian skin secretions. These peptides have a variety of actions including antibiotic and anticancer activities and the inhibition of neuronal nitric oxide synthase. We have investigated the structure-activity relationship of citropin 1.1, a broad-spectrum antibiotic and anticancer agent that also causes inhibition of neuronal nitric oxide synthase, by making a number of synthetically modified analogues. Citropin 1.1 has been shown previously to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
1
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 83 publications
2
60
1
2
Order By: Relevance
“…In previous studies, α-helical peptides were shown to need more than 20 amino acid residues to span the entire thickness of the eukaryotic cell membranes for the barrel-stave mechanism (29,30). Thus, the relatively small size of HaA4 along with aurein 1.2 (31) and citropin 1.1 (32), isolated from frogs suggest that these AMPs mediate their membranolytic effect through the carpet mechanism (33). In addition, it has been reported that bovine lactoferricin binds to the cell membrane and causes cell membrane disruption followed by entry of the peptide to the cytoplasm of Jurkat T-leukemia cells and damage to mitochondrial membrane (34).…”
Section: Haa4 Induces Apoptosis In the Leukemia Cells Via A Caspasedementioning
confidence: 99%
“…In previous studies, α-helical peptides were shown to need more than 20 amino acid residues to span the entire thickness of the eukaryotic cell membranes for the barrel-stave mechanism (29,30). Thus, the relatively small size of HaA4 along with aurein 1.2 (31) and citropin 1.1 (32), isolated from frogs suggest that these AMPs mediate their membranolytic effect through the carpet mechanism (33). In addition, it has been reported that bovine lactoferricin binds to the cell membrane and causes cell membrane disruption followed by entry of the peptide to the cytoplasm of Jurkat T-leukemia cells and damage to mitochondrial membrane (34).…”
Section: Haa4 Induces Apoptosis In the Leukemia Cells Via A Caspasedementioning
confidence: 99%
“…The structural diversity of polypeptides secreted from amphibian dermal granular glands is probably reflective of a plethora of different biological functions, including the regulation of skin physiology, defense against predators, or prevention of skin colonization/infection by microorganisms (1). Of particular note has been the focused effort, during the last decade, of several studies which have reported the host defense peptides exuded in secretions from dorsal glands of some 20 species of Australian anurans, including species from the genera Litoria and Uperoleia (3,5,18). Uperin 3.6 is a wide-spectrum antibiotic peptide isolated from the Australian toadlet Uperoleia mjobergii.…”
mentioning
confidence: 99%
“…Uperin 3.6 is one of the most potent membrane-active antimicrobial peptides isolated from amphibians. It adopts an amphipathic ␣-helical structure along its entire length with no central region of enhanced flexibility, a feature commonly found in cationic peptides (3,5,18).…”
mentioning
confidence: 99%
“…Natural products of other amphibian as Bombina variegate have demonstrated interesting results against several types of neoplastic cell lines (Doyle et al, 2003;Kamano et al, 2002). The extract of the skin and the secretions of other amphibian species Bufo bufo gargarizans Cantor (Bufonidae) are used in the preparation of the Chinese traditional remedy Chan Su, used against several illnesses and with an antineoplastic activity reported by several articles, mainly due the alkaloid bufagin, a natural product that can affect several mechanisms involved on the cell proliferation (Hashimoto et al, 1997;Akiyama et al, 1999;Yeh et al, 2003;Nasu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%